Efektivitas Penggunaan Media Pembelajaran Berbasis Video melalui Website Rumah Belajar pada Materi Teks Eksplanasi - Wahyuni, Janetri Suti; Haryadi, Haryadi; Nuryatin, Agus (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Video as a learning medium is a form of innovation in the field of technology to improve the quality of education. The Rumah Belajar website provides learning video media as a form of government support for the quality of education in Indonesia. The purpose of this study is to describe the effectiveness of video-based learning media through the home study website on explanatory text material. This research is quantitative descriptive. The research sample was 14 students of class XI at SMA Negeri 3 Bengkulu City. The data collection technique was simple random sampling using a questionnaire. The data analysis technique in this study is descriptive statistics by testing the validity and reliability of the instrument. The results of the questionnaire were analyzed on a percentage basis to reveal indicators of student responses to video-based learning media. The results of this study indicate that the effectiveness of video as a learning media from (1) the material aspect 85.71% (very effective), (2) the suitability aspect of the video 94.28% (very effective), (3) the video experimental aspect 90% (very effective), and (4) usability aspect 89.64% (very effective). The results show an average of 89% including the very effective category.